A formação do Controller: contribuição para a formação do Controller a partir do curso de Graduação em Ciências Contábeis - Oliveira, Elaine Rosa de (2015)
At present, the market requires a professional ready to take on new responsibilities. Such a reality also makes it necessary that he/she continuously develop more skills and qualifications. Then, a question emerges as to whether colleges can catch up with such constant dynamism in their subject curriculum in order to equip students with adequate training that would make them critical and able to guide the administration so as to keep business along the planned route. This investigation presents a critical analysis of the Controller education. The research aimed to learn how the training of this professional takes place so he/she can fill this position. Through bibliographical research, it was identified the profile of higher education in Controlling in Brazil, the performance of the Controller in the Controller s office and skills recognized as necessary to this professional. Data were collected regarding the curricula of three institutions of higher education in Accounting, considered the best in the job market, and which disclose their curriculum. They are UFMG, USP and Mackenzie. The content of these curricula was confronted with the skills, deemed, in the literature, as the ones desired from a Controller. Comparison of these two sources revealed that a relevant part of the attributes that the Controller must possess is not addressed in the subjects of higher education in Accounting. The main deficiencies identified in the curricula were disciplines that approach behavioral development. Thus, a proposal to improve the training of professionals has been outlined. It was appointed that search for coaching and, if possible, mentoring is necessary since it was understood that if behavior should be changed, it must take place beyond the professional life. Finally, some suggestions are made for additional training for those who wish to successfully fill the Controller position, so as to improve their technical and behavioral skills